ANALISIS PENGARUH KETERLAMBATAN PENYELESAIAN PROYEK KONSTRUKSI DENGAN MENGGUNAKAN METODE EARNED VALUE : STUDI KASUS: PROYEK PENAMBAHAN GEDUNG LANTAI DUA UNIVERSITAS TOMPOTIKA LUWUK - suartana, putu; Susilawati, Sri; Okayana, Komang (SIPARSTIKA: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2025)
Construction Project is an activity carried out with limited time and resources to achieve the specified end result. In the implementation of a Construction Project, delays often occur where the actual progress of the realization obtained does not match the planned progress. So that it can affect the costs that have been budgeted. This research was conducted at Tompotika University Luwuk Banggai Jl. Dewi Sartika No. 67 Kelurahan Luwuk, Banggai Regency, Central Sulawesi Province. This study aims to determine the factors that cause delays in the project, as well as the impact of the influence of delays on costs in the Addition of the Second Floor Building Project of Tompotika University Luwuk Banggai. The method used in this study is descriptive quantitative, with the analysis tool used is Earned Value (EV) or Result Value. The results of the study indicate that the main factors causing delays in the Second Floor Building Addition Project of Tompotika University Luwuk Banggai are the implementation of the planned project scheduling is not good, so that the weight of the work realization in the field is not able to reach the weight of the work that has been planned. After conducting an analysis using the Earned Value (EV) method, in the calculation of basic indicators, as well as the calculation of the combination of variance values and performance indexes, it was found that the Second Floor Building Addition Project of Tompotika University Luwuk Banggai, incurred more wasteful actual costs (Over Cost) in the 1st week, which was Rp 17,714,858.82 from the realized cost of Rp 17,699,315.67 with a difference = -15,507.15. However, in the 2nd week to the 16th week, the costs incurred were more economical, namely Rp1,949,701,273.09 from the realization cost of Rp1,957,340,068.05 with a difference = 7,638,794.69. Meanwhile, the project schedule experienced a total delay from week 1 to week 16.